Workers' housing estates in postindustrial cities - modernization or revitalization? = Osiedla robotnicze w miastach postindustrialnych - modernizacja czy rewitalizacja? - Gaweł, Dariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents a part of the results on the physiognomy of a postindustrial city under conditions of economic transformation in Poland. The study area encompasses industrial centers located in the region of the Central Industrial District (Centralny Okręg Przemysłowy - COP) in the Świętokrzystkie and Mazowieckie voivodeships (districts). The specific urban structure of the industrial city and unemployment among its inhabitants resulting from ownership transformations generate various problems.
Keywords: osiedla robotnicze; miasto postindustrialne; modernizacja; rewitalizacja; workers housing estates; postindustrial city; modernization; revitalisation